The Contribution of Literature in the Humanization of the Law in Indonesia - Tatit Hariyanti (Humaniora, 2013)
Law and Literature movement has been developing in western countries since the first half of the twentieth century as the response of the isolation of law from other disciplines and the idea of humanizing law to have optimal function for the betterment of  social order. This movement exerts great potentials in developing methods of teaching and interpreting legal texts resulting in the betterment of the performance of the law makers and the deeper understanding of law. The isolation also  happens in Indonesia; however, there is not  obvious  echo of the movement  in Indonesia. There is no place of  literature in Indonesians law. Under the movement of law and literature, this qualitative research aims not at finding out the reason of excluding literature from law; instead it aims at demontrating and promoting that literature could give contribution in   understanding and producing humanistic legal texts in Indonesia.  Taking available data by heuristic model and comparative and descriptive analysis, this research concludes that literary works could provide sources of  learning and understanding  law, and  literary theories could be applied in improving the making of more humanistic legal texts in Indonesia.